Idea, Identity and Interesubjective Means of India Act East Foreign Policy towards Taiwan - Auliyah, Ulul Azmiati; Suharman, Yoga; Kuswardini, Seftina; Hasymi, Aditya Maulana (Jurnal Studi Diplomasi dan Keamanan, 2023)
This article aims to examine the reason why India is continuing to maintain cooperation with Taiwan through the “Act East” policy, even though it has not provided high benefits for India? In order to answer the question, this article employed a constructivism perspective related to foreign policy analysis. In constructivism foreign policy analysis, ideas and identity are vital for the state. India's “Act East” towards Taiwan reflects some element of constructivism which encompass ideas, national identity and intersubjective means that influences preference, policy choice and state interest. The first, India’s “Act East” is an idea to revive strategic and historical relations with Taiwan. Second, the positive India-Taiwan intersubjective process formed a shared understanding based on the values of freedom, democracy, human rights, and the norms. Third, the national identity as an emerging power puts India to coexist peacefully with Taiwan and maintain security as well as stability in the region.